Geografski informacijski sistemi v Sloveniji 2007-2008 - Čeh, Marjan; Hladnik, David; Krevs, Marko; Perko, Drago; Podobnikar, Tomaž; Razpotnik, Nika; Stančič, Zoran; Zorn, Matija (GIS v Sloveniji, 2008)
A monograph, ninth in a row, in 42 scientific and professional articles presents on overview of temporary use of geographic information systems (GIS) in Slovenia.Many possibilities of their use are introduced~three-quarters of all articles present applicability of GIS. Furthermore possibilities of their use in geography, geology, geodesy, cartography, pedology, biology, forestry, civil engineering, and hydrology are introduced, as well their use in dialectology, archeology, history, by cultural heritage and natural hazards research and in addition also the use in spatial planning.